Considering climate and conflict conditions together to improve interventions that prevent child acute malnutrition. Issue 9 (September 2021) - Brown, Molly E; Grace, Kathryn; Billing, Trey; Backer, David
Summary: Despite early warning signs about threats to food security, humanitarian interventions often lag behind these warning signs. Climate and conflict conditions are among the most important factors preceding food system failures and malnutrition crises around the world. Research shows how conflict and climate conditions can upend functional food and economic systems, but this research does not address the severe health impacts of these conditions on infants and young children. Translating quantitative research findings into humanitarian interventions requires geographical detail, resulting in location-specific alerts of risks of food insecurity. We describe how the use of readily available, spatially referenced quantitative data can support targeted interventions for nutrition resiliency. Effective humanitarian programmes for targeted nutrition interventions require real-time datasets on food security drivers and models that can provide actionable guidance to mitigate negative impacts of conflict and climate conditions on the people most susceptible to food insecurity. Although treatment of acute malnutrition is important, treating existing malnutrition is not enough. Instead, action to prevent acute malnutrition should be taken to minimise suffering and to maximise wellbeing, particularly in contexts prone to worsening climate and conflict conditions.